Lanthanide (III) complexes of 3-(ethylthio)phenyl-substituted phthalocyanines: Synthesis and physicochemical properties. (September 2018) - Dubinina, Tatiana V.; Tychinsky, Pavel I.; Borisova, Nataliya E.; Krasovskii, Vitaly I.; Ivanov, Anton S.; Savilov, Serguei V.; Maklakov, Sergey S.; Sedova, Marina V.; Tomilova, Larisa G.
Abstract: Novel phthalocyaninates of terbium, erbium and lutetium, bearing 3-(ethylthio)phenyl peripheral groups, were synthesised with high yields. The complexes obtained were characterised by 1 H nuclear magnetic resonance spectroscopy, Fourier-transform infrared spectroscopy and high-resolution mass spectrometry. Thermal stability of the lanthanide complexes was examined using thermogravimetric analysis combined with fourier-transform infrared spectroscopy. Strong upfield (up to −59.06) and downfield (up to 22.32) lanthanide-induced shifts of signals of aromatic protons were observed in nuclear magnetic resonance spectra of terbium and erbium complexes respectively. It was shown, that comparing to phenyl-substituted analogues the introduction of ethylthio-moieties in the meta-positions of phenyl substituents does not affect the Q band maxima. Hybrid gold nanoparticles coated with molecules of the lutetium complex were obtained and their optical properties were studied. The formation of phthalocyanine shell and its composition were proven using atomic force and transmission electron microscopy. Absorption cross-sections of ground and the first excited states were calculated using the data of open-aperture z-scan measurements for lutetium complex and hybrid gold nanoparticles on its basis. Graphical abstract: Highlights: 3-(Ethylthio)phenyl-substituted phthalocyaninates of lanthanides were synthesised. Strong up- and downfield lanthanide-induced shifts of protons were observed. Au nanoparticles coated with molecules of lutetium phthalocyaninate were obtained. Presence of Au particles leads to aggregation of phthalocyanines around Au core. Absorption cross-sections of ground and first excited states were calculated.